Tick-borne encephalitis vaccination in multiple sclerosis: A prospective, multicenter study. Issue 2 (March 2020) - Winkelmann, Alexander; Metze, Christoph; Frimmel, Silvius; Reisinger, Emil C.; Zettl, Uwe K.; Loebermann, Micha
Abstract : Objective: To assess the changes in disease activity after tick-borne encephalitis (TBE) vaccination in patients with multiple sclerosis (MS) on a variety of disease-modifying drugs and to assess the immunogenicity, safety, and clinical tolerability of the vaccine in this patient group. Methods: We conducted a prospective, multicenter, nonrandomized observational study. We enrolled 20 patients with MS receiving TBE vaccination who had been on disease-modifying treatment (DMT) for at least 6 months. Serum samples were obtained before and after 4 weeks of vaccination to determine the specific TBE antibody response. MS disease activity (Expanded Disability Status Scale and relapse rates) was evaluated for 1 year after immunization. Local and systemic adverse events were registered. Results: In 20 subjects with TBE vaccination, the annualized relapse rate decreased from 0.65 in the year before vaccination to 0.21 in the following year. Expanded Disability Status Scale remained stable during the 2-year period before vaccination and 1 year after vaccination (range: 1.50–1.97). The geometric mean titer (GMT) increased from 169 Vienna units per milliliter (VIEU/mL) to 719 VIEU/mL 4 weeks after vaccination ( p = 0.001), and 77.8% had protective antibody titers after vaccination. In 9 patients treated with beta interferons, GMT increased from 181 VIEU/mL to 690 VIEU/mL ( p = 0.018). Three subjects treated with glatiramer acetate developed a 2- to 9.6-fold increase. Patients treated with fingolimod developed the lowest increase in antibody titer. Conclusion: TBE vaccination showed good tolerability and was safe in patients with MS. MS disease activity was not increased, and annualized relapse rates decreased after vaccination. Vaccine response differs according to the underlying DMT. Trial registration: ClinicalTrials.gov, clinicaltrials.gov, Identifier: NCT02275741.